Loss of MLK3 signaling impedes ulcer healing by modulating MAPK signaling in mouse intestinal mucosa - Kovalenko, Pavlo L. (American Physiological Society, 2012)
Mixed-lineage kinase 3 (MLK3) activates multiple MAPK pathways and can initiate apoptosis, proliferation, migration, or differentiation in different cell types. However, whether MLK3 signaling regulates intestinal epithelial cell sheet migration in vivo is not known. We sought to investigate whether MLK3 signaling is important in intestinal mucosal healing and epithelial cell motility in vivo and in vitro. In vivo, we compared the healing of jejunal mucosal ulcers induced in MLK3 knockout (KO) mice with healing in wild-type (WT) mice. Ulcer healing was 20.8% less at day 3 (P < 0.05) and 18.9% less at day 5 (P < 0.05) in MLK3 KO than WT mice. Within the intestinal mucosa of MLK3 KO mice, ERK and JNK signaling were reduced, phosphatase and tensin homolog deleted on chromosome 10 (PTEN) level was increased, and p38 signaling was unchanged. Parallel in vitro studies using an MLK inhibitor assessed the role of MLK signaling in human Caco-2 intestinal epithelial migration across collagen substrates. The MLK inhibitor reduced closure of circular wounds in Caco-2 monolayers. MLK inhibition reduced ERK and JNK, but not p38, signaling in Caco-2 cells. Although PTEN is increased after MLK inhibition, it does not influence MLK-mediated cell migration. These findings indicate that disruption of MLK3 signaling impairs ulcer healing by suppressing ERK and JNK signaling in vitro and in mouse intestinal mucosa in vivo. These results reveal a novel role for MLK3 signaling in the regulation of intestinal epithelial migration in vivo and suggest that MLK3 may be an important target for the regulation of intestinal mucosal healing.